Centro educativo básico especial en Ventanilla - Soto Pizzali, Veronica Antonella (2022)
The project to be developed is a Special Basic Educational Center in the Ventanilla district, in the southern sector. Its purpose is to generate a response to the educational need, being a procedural tool for learning and cognitive development through the architectural space; enhancing the diversity of learning and responding to the spatial need of users with different disabilities; and that of their social integration with the community. It is a proposal that enhances learning through connection with society. Including the educational program, a cultural and recreational approach that complements it. Likewise, it seeks to reduce the deficit of the special basic educational service and offer the possibility of continuing to grow by proposing the project as a tool that seeks to integrate children with different disabilities, responding to the spatial need, reception of cognitive level and that of their integration to society, and not just include it in a context that is not adequate to meet its needs.